BIBB international : strategy paper on the internationlisation of German vocational education and training - Dybowski, Gisela [Verfasser]; Hanf, Georg [Verfasser]; Walter, Matthias [Verfasser] (Bundesinstitut für Berufsbildung, 2007)
"The process of internatiolisation has gathered pace in recent years, spreading through one area of society after another and posing new challanges, not least for vocational education and training (VET). The growing globalisation of the economy and the rapid process of European integration towards a single market for education and employment have given rise to a radically new situation. National VET systems are caught in a cross-current between the imperative of international competition and the necessity for cross-border cooperation. At the same time, there are increasingly stringent requirements for the planning of VET to embrace a European and an international outlook. The paper explains the action to be taken by the Federal Institute for Vocational Education and Training (BIBB) in response to these developments." (BIBB)
Keywords: I 1 Internationale Berufsbildung; S 2.3 Berufsbildungspolitik; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Berufsbildung; Internationalisierung; Internationale Zusammenarbeit; Europäische Integration; Berufsbildungspolitik; Strategie; Bundesinstitut für Berufsbildung